Effect of Combining Food and Sex Attractants on the Capture of Dacus oleae Flies - Haniotakis, G.E.; Vassiliou-Waite Α. (ENTOMOLOGIA HELLENICA, 1987)
Sex pheromonal compounds i.e. the most potent male attractants, and ammonia, one of the most potent female attractants available today for Dacus oleae (Gmelin), were combined on the same trap. This combination resulted in an overall increase of female captures as compared to those of ammonia alone, but a decrease of male captures as compared to those of pheromone alone. Deviations from this overall effect were observed during certain periods of the year and are caused by varying environmental and biological factors which influence insect response to pheromones. Explanations for these results based on recent findings concerning the pheromone system of D. oleae are presented here.